Intuitive human interface to a scanning tunnelling microscope: observation of parity oscillations for a single atomic chain - Tewari, Sumit; Bakermans, Jacob; Wagner, Christian; Galli, Federica; van Ruitenbeek, Jan M. (Beilstein Journal of Nanotechnology, 2019)
A new way to control individual molecules and monoatomic chains is devised by preparing a human–machine augmented system in which the operator and the machine are connected by a real-time simulation. Here, a 3D motion control system is integrated with an ultra-high vacuum (UHV) low-temperature scanning tunnelling microscope (STM). Moreover, we coupled a real-time molecular dynamics (MD) simulation to the motion control system that provides a continuous visual feedback to the operator during atomic manipulation. This allows the operator to become a part of the experiment and to make any adaptable tip trajectory that could be useful for atomic manipulation in three dimensions. The strength of this system is demonstrated by preparing and lifting a monoatomic chain of gold atoms from a Au(111) surface in a well-controlled manner. We have demonstrated the existence of Fabry–Pérot-type electronic oscillations in such a monoatomic chain of gold atoms and determined its phase, which was difficult to ascertain previously. We also show here a new geometric procedure to infer the adatom positions and therefore information about the substrate atoms, which are not easily visible on clean metallic surfaces such as gold. This method enables a new controlled atom manipulation technique, which we will refer to as point contact pushing (PCP) technique.
Keywords: adatom imaging; mechanical annealing; scanning tunnelling microscopy (STM); STM tip; tip apex

(untitled) - Xu, B.; Tao, N. J. (Science, 2003)

(untitled) - Fournier, N.; Wagner, C.; Weiss, C.; Temirov, R.; Tautz, F. S. (Phys. Rev. B, 2011)

(untitled) - Fujihira, M.; Suzuki, M.; Fujii, S.; Nishikawa, A. (Phys. Chem. Chem. Phys., 2006)

(untitled) - Li, C.; Pobelov, I.; Wandlowski, T.; Bagrets, A.; Arnold, A.; Evers, F. (J. Am. Chem. Soc., 2008)

(untitled) - Green, M. F. B.; Esat, T.; Wagner, C.; Leinen, P.; Grötsch, A.; Tautz, F. S.; Temirov, R. (Beilstein J. Nanotechnol., 2014)

(untitled) - Leinen, P.; Green, M. F. B.; Esat, T.; Wagner, C.; Tautz, F. S.; Temirov, R. (Beilstein J. Nanotechnol., 2015)

(untitled) - Stroscio, J. A.; Celotta, R. J. (Science, 2004)

(untitled) - Smit, R. H. M.; Untiedt, C.; Rubio-Bollinger, G.; Segers, R. C.; van Ruitenbeek, J. M. (Phys. Rev. Lett., 2003)

Magnetism of a single atom - Otte, A. F. (Leiden Institute of Physics (LION), Leiden University, 2008)

Complex oxides studied by scanning tunneling microscopy/spectroscopy - Kelly, S. J. (Ph.D. Thesis, Leiden Institute of Physics (LION), Leiden University, 2012)

(untitled) - Oliver, D. J.; Paul, W.; El Ouali, M.; Hagedorn, T.; Miyahara, Y.; Qi, Y.; Grütter, P. H. (Nanotechnology, 2014)

(untitled) - Moresco, F.; Gross, L.; Alemani, M.; Rieder, K.-H.; Tang, H.; Gourdon, A.; Joachim, C. (Phys. Rev. Lett., 2003)

(untitled) - Moresco, F. (Phys. Rep., 2004)

(untitled) - Moresco, F.; Gross, L.; Grill, L.; Alemani, M.; Gourdon, A.; Joachim, C.; Rieder, K. H. (Appl. Phys. A: Mater. Sci. Process., 2005)

(untitled) - Kröger, J.; Jensen, H.; Berndt, R. (New J. Phys., 2007)

(untitled) - Hla, S. W. (Rep. Prog. Phys., 2014)

(untitled) - Yang, J.; Sordes, D.; Kolmer, M.; Martrou, D.; Joachim, C. (Eur. Phys. J.: Appl. Phys., 2016)

(untitled) - Tewari, S.; Bastiaans, K. M.; Allan, M. P.; van Ruitenbeek, J. M. (Beilstein J. Nanotechnol., 2017)

Atomic and Nanometer-Scale Modification of Materials: Fundamentals and Applications - Avouris, P. (Springer Netherlands, 1993)

(untitled) - Tománek, D.; Aligia, A. A.; Balseiro, C. A. (Phys. Rev. B, 1985)

(untitled) - Cortes-Huerto, R.; Sondon, T.; Saúl, A. (Phys. Rev. B, 2013)

(untitled) - Cleri, F.; Rosato, V. (Phys. Rev. B, 1993)

Simple and Fast Multimedia Library

(untitled) - Trevethan, T.; Kantorovich, L. (Nanotechnology, 2005)

(untitled) - Berendsen, H. J. C.; Postma, J. P. M.; van Gunsteren, W. F.; DiNola, A.; Haak, J. R. (J. Chem. Phys., 1984)

Advanced Computer Simulation - Hünenberger, P. H. (Thermostat algorithms for molecular dynamics simulations, 2005)

(untitled) - Henriksson, K. O. E.; Nordlund, K.; Keinonen, J. (Phys. Rev. B, 2005)

Molecular modelling: principles and applications - Leach, A. R. (Pearson, 2001)

(untitled) - Tartaglini, E.; Verhagen, T. G. A.; Galli, F.; Trouwborst, M. L.; Müller, R.; Shiota, T.; Aarts, J.; van Ruitenbeek, J. M. (Low Temp. Phys., 2013)

(untitled) - Yanson, A. I.; Bollinger, G. R.; van den Brom, H. E.; Agraït, N.; van Ruitenbeek, J. M. (Nature, 1998)

(untitled) - Ohnishi, H.; Kondo, Y.; Takayanagi, K. (Nature, 1998)

(untitled) - Agraït, N.; Yeyati, A. L.; van Ruitenbeek, J. M. (Phys. Rep., 2003)

Molecular Electronics - Cuevas, J. C.; Scheer, E. (World Scientific Publishing Co Pte Ltd, 2010)

(untitled) - Wintterlin, J.; Wiechers, J.; Brune, H.; Gritsch, T.; Höfer, H.; Behm, R. J. (Phys. Rev. Lett., 1989)

(untitled) - Zheng, N. J.; Tsong, I. S. T. (Phys. Rev. B, 1990)

(untitled) - Gimzewski, J. K.; Berndt, R.; Schlittler, R. R. (Ultramicroscopy, 1992)

(untitled) - Zhang, Y.-h.; Wahl, P.; Kern, K. (Nano Lett., 2011)

(untitled) - Böhringer, M.; Schneider, W.-D.; Glöckler, K.; Umbach, E.; Berndt, R. (Surf. Sci., 1998)

(untitled) - Hla, S.-W.; Braun, K.-F.; Rieder, K.-H. (Phys. Rev. B, 2003)

(untitled) - Limot, L.; Kröger, J.; Berndt, R.; Garcia-Lekue, A.; Hofer, W. A. (Phys. Rev. Lett., 2005)

(untitled) - Kröger, J.; Néel, N.; Sperl, A.; Wang, Y. F.; Berndt, R. (New J. Phys., 2009)

(untitled) - Hofer, W. A.; Fisher, A. J.; Wolkow, R. A.; Grütter, P. (Phys. Rev. Lett., 2001)

(untitled) - Calvo, M. R.; Sabater, C.; Dednam, W.; Lombardi, E. B.; Caturla, M. J.; Untiedt, C. (Phys. Rev. Lett., 2018)

(untitled) - Sabater, C.; Dednam, W.; Calvo, M. R.; Fernández, M. A.; Untiedt, C.; Caturla, M. J. (Phys. Rev. B, 2018)

(untitled) - Stroscio, J. A.; Eigler, D. M. (Science, 1991)

(untitled) - Eigler, D. M.; Lutz, C. P.; Rudge, W. E. (Nature, 1991)

(untitled) - Avouris, P. (Acc. Chem. Res., 1995)

WebElements Periodic Table –Gold– radii of atoms and ions

(untitled) - Smit, R. H. M.; Noat, Y.; Untiedt, C.; Lang, N. D.; van Hemert, M. C.; van Ruitenbeek, J. M. (Nature, 2002)

From Quantum Point Contacts to Monatomic Chains:Fabrication and Characterization of the Ultimate Nanowire - Smit, R. H. M. (Leiden Institute of Physics (LION), Leiden University, 2003)

(untitled) - Lang, N. D. (Phys. Rev. Lett., 1997)

(untitled) - Brandbyge, M.; Kobayashi, N.; Tsukada, M. (Phys. Rev. B, 1999)

(untitled) - Gutierrez, R.; Grossmann, F.; Schmidt, R. (Acta Phys. Pol., B, 2001)

(untitled) - Havu, P.; Torsti, T.; Puska, M. J.; Nieminen, R. M. (Phys. Rev. B, 2002)

(untitled) - Lee, Y. J.; Brandbyge, M.; Puska, M. J.; Taylor, J.; Stokbro, K.; Nieminen, R. M. (Phys. Rev. B, 2004)

(untitled) - Todorov, T. N.; Sutton, A. P. (Phys. Rev. B, 1996)

(untitled) - Heinz, H.; Vaia, R. A.; Farmer, B. L.; Naik, R. R. (J. Phys. Chem. C, 2008)

(untitled) - van Vreumingen, D.; Tewari, S.; Verbeek, F.; van Ruitenbeek, J. (Micromachines, 2018)

(untitled) - Wagner, C.; Fournier, N.; Tautz, F. S.; Temirov, R. (Phys. Rev. Lett., 2012)

(untitled) - Wagner, C.; Fournier, N.; Ruiz, V. G.; Li, C.; Müllen, K.; Rohlfing, M.; Tkatchenko, A.; Temirov, R.; Tautz, F. S. (Nat. Commun., 2014)